2020
DOI: 10.1007/s12144-020-01191-4
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and PTSD among children and their parent during 2019 novel coronavirus disease (COVID-19) outbreak in China

Abstract: Home quarantine may lead to families developing a variety of psychological distress. The purpose of this study was to examine the psychological status of children and their parent during 2019 coronavirus disease (COVID-19) outbreak in China. Data were collected from children ( n = 1360) and their parent ( n = 1360) in China using online survey during February 2020. Demographic information, media exposure, and psychological status including anxiety, depression and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
18

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(173 citation statements)
references
References 39 publications
4
131
0
18
Order By: Relevance
“…In addition, general conflict, poor family functioning and martial distress emerged as significant risk factors for perinatal anxiety during the pandemic ( 56 , 72 , 74 , 81 , 89 , 98 , 116 , 117 , 128 ). Pregnant women's own health anxiety ( 81 , 98 , 103 , 117 , 118 , 129 ) and partner's perceived fear of COVID-19 ( 116 ) were understood to be contributing to pregnant women's increased anxiety and preventative behavior such as increased hygiene practices and social distancing ( 62 , 71 , 116 , 134 ). Women strictly adhering to the rules and safety recommendations reported greater symptoms ( 98 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, general conflict, poor family functioning and martial distress emerged as significant risk factors for perinatal anxiety during the pandemic ( 56 , 72 , 74 , 81 , 89 , 98 , 116 , 117 , 128 ). Pregnant women's own health anxiety ( 81 , 98 , 103 , 117 , 118 , 129 ) and partner's perceived fear of COVID-19 ( 116 ) were understood to be contributing to pregnant women's increased anxiety and preventative behavior such as increased hygiene practices and social distancing ( 62 , 71 , 116 , 134 ). Women strictly adhering to the rules and safety recommendations reported greater symptoms ( 98 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies exploring the role of gender in the management of anxiety during the COVID-19 pandemic found that gender was a risk factor for depression and anxiety symptoms (Fong & Iarocci, 2020;Yue et al, 2020). Preliminary findings indicate that girls and women were hit harder during the pandemic (Fong & Iarocci, 2020;Yue et al, 2020).…”
Section: Children's Wellbeingmentioning
confidence: 94%
“…This has led to the recent growing interest in the psychological manifestations of the pandemic (Ashikkali, Carroll, & Johnson, 2020;Sprang & Silman, 2013). Indeed, strong evidence confirms the profound psychological impacts lockdowns and isolation on humanity (Brooks et al, 2020;Garcia de Avila et al, 2020;Hawke et al, 2020;Roy et al, 2020;Yue, Zang, Le, & An, 2020). Prior research has consistently shown that families who were either isolated, or quarantined, during the H1N1 pandemic, in the United States, experienced post-traumatic stress disorder (PTSD) symptoms and anxiety (Sprang & Silman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Children who are protected by women at home do not have a relatively negative psychological experience. Therefore, parents sharing the responsibility of raising children together becomes an important factor in protecting the mental health of the family (Yue et al, 2020). Long-term social distancing also leads to an increase in domestic violence, which is believed to be caused by weakened resilience and increased stress.…”
Section: ⅱ Psychological Symptoms Caused By Covid-19mentioning
confidence: 99%